2021
DOI: 10.2147/ndt.s324968
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Physician Perspectives of Depressive Symptoms and Expectations for Treatment Outcome: Results from a Web-Based Survey

Abstract: Purpose A previous international study suggested that perceptions of depression symptoms, social function, and treatment expectations are different between patients/physicians. We aimed to examine whether such differences exist in Japan. Methods A web-based survey was conducted with patients who reported that they had been diagnosed with depression, and physicians who reported that they had treated patients with depression, in Japan. Questionnaires were designed to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Other studies have also shown clinically relevant differences between patient and HCP perceptions in depression [ 17 21 ]. This may be of clinical significance, as discordance between patient and physician perceptions has been shown to be associated with poorer treatment outcomes in patients with depression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown clinically relevant differences between patient and HCP perceptions in depression [ 17 21 ]. This may be of clinical significance, as discordance between patient and physician perceptions has been shown to be associated with poorer treatment outcomes in patients with depression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient-centered care in managing mental health disorders such as depression is well-recognized [ 11 16 ]. However, studies have shown that differences exist between the perspectives of patients with depression and their healthcare providers (HCPs) regarding the importance and impact of symptoms experienced and treatment goals [ 17 21 ]. Data on HCP perspectives on the prevalence of emotional blunting and its impact on activities of daily living in patients with depression are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…J. Ishigooka и соавт. [14] по результатам онлайн-опроса пациентов и врачей установили, что когнитивные симптомы депрессии способны распознать только 82% врачей в случае тяжелой депрессии и 54% -при легких формах. Среди врачей 15% не были осведомлены о возможных соматических проявлениях депрессии.…”
unclassified